Nowoczesność w majątkach ziemiańskich na Podlasiu w XIX–XX w. - Chyra-Rolicz, Zofia (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
Podlasie at the second half of 19th century has been a territory undeveloped, land of back warded agriculture, traditional three-field system of cultivation and lack of visible enterprises of food processing. Trade and credit services were in Jewish hands. The usury was an intense calamity all groups of society. The great national tragedy – collapse of the January insurrection of 1863 and the enfranchisement of peasants done by the tsar authority consolidated the feeling of hopelessness, very difficult to overcome. Under the influence of Positivism ideas ad propaganda of everyday work for developing the civilization level of the country, in the circle of aristocracy and intelligentsia we can observe the firth proofs of modernization of nobles’ manors, better agriculture, beginning of new crow cultures, horticulture, plantations of sugar beet roots, willows and potatoes, using of modern agricultural tools. The landlords and middle manors’ owners, also tenants had invested into melioration of lands, developing of apiculture and honey – processing, cattle and poultry breeding, also fishery farming. It had appeared early establishing of food processing enterprises such as sugar-works, oil mills, ponds. The Agricultural Society in the province of Siedlce, established by prince Władysław Światopełk-Czetwertyński, had taken the big role in cultivation of civilization progress on Podlasie. The Society propagated establishing agricultural circles, usually provided by landlords, jointed landlords and peasants in common work on developing the country and promoting the agricultural education. Agricultural circles promoted also common, co-operative economic activity, such as agricultural shops, saving and credit, chaises, dairy. There were the first step into taking their matters in their hands, building social links and the origin of new the Polish citizen’s society.